Seroprevalence of Helicobacter pylori infection among an adult population of Lima, Peru 2017 - Pareja Cruz, Arturo (2017)
Objective: To know the seroprevalence of Helicobacter pylori infection among an adult population of Lima, Peru 2017. Materials and methods: Descriptive, prospective, cross-sectional study. Population of volunteers older than 18 years, of both sexes, with or without general gastrointestinal discomfort. A screening campaign was carried out in the districts of Magdalena and Chorrillos in the city of Lima, Peru, in January 2017. For the diagnosis, CTK Biotech’s OnSite H. pylori Ab Combo Rapid Test CE was used. Results: One hundred forty (140) patients were evaluated, with a mean age of 36.6 years old, being 22.1% male and 77.9% female. The seroprevalence of Helicobacter pylori infection was 63.6%. Conclusions: We conclude that Helicobacter pylori infection is common in the city of Lima, with no difference between gender and age.